Applying the Retro‐Enantio Approach To Obtain a Peptide Capable of Overcoming the Blood–Brain Barrier1. Issue 13 (4th February 2015) - Prades, Roger; Oller‐Salvia, Benjamí; Schwarzmaier, Susanne M.; Selva, Javier; Moros, María; Balbi, Matilde; Grazú, Valeria; de La Fuente, Jesus M.; Egea, Gustavo; Plesnila, Nikolaus; Teixidó, Meritxell; Giralt, Ernest
Abstract The blood–brain barrier (BBB) is a formidable physical and enzymatic barrier that tightly controls the passage of molecules from the blood to the brain. In fact, less than 2 % of all potential neurotherapeutics are able to cross it. Here, by applying the retro‐enantio approach to a peptide that targets the transferrin receptor, a full protease‐resistant peptide with the capacity to act as a BBB shuttle was obtained and thus enabled the transport of a variety of cargos into the central nervous system.